Managing the Precarious Hemostatic Balance during Extracorporeal Life Support: Implications for Coagulation Laboratories - Winkler, Anne M. (Seminars in Thrombosis and Hemostasis, 2017)
For the past four decades, extracorporeal life support (ECLS) has been used to treat critically ill adult and pediatric patients with cardiac and/or respiratory failure unresponsive to medical management, and there are increasing numbers of centers performing ECLS for numerous indications worldwide. Despite the progress with advancing technology, hemorrhagic and thrombotic complications occur frequently and are associated with worse outcomes, but the exact cause is often elusive or multifactorial. As a result of the interaction between blood and a nonendothelialized circuit, there is activation of coagulation, fibrinolysis, as well as an increased inflammatory response; thus, anticoagulation of the patient and circuit is necessary. While unfractionated heparin (UFH) remains the mainstay anticoagulant used during ECLS, there is a paucity of published data to develop a universal anticoagulation guideline and centers are forced to create individualized protocols to guide anticoagulation management, frequently while lacking expertise. From an international survey, centers often use a combination of tests to guide management, which in turn can lead to discordant results and confused management. Studies are urgently needed to investigate optimization of current anticoagulation strategies with UFH, as well as use of alternative anticoagulants and nonthrombogenic biomaterials.
Keywords: extracorporeal life support; extracorporeal membrane oxygenation; anticoagulation; heparin monitoring